Gotham High - De la Cruz, Melissa, 1971- (DC Comics, 2020)
After being kicked out of his boarding school, 17-year-old Bruce Wayne returns to Gotham City to find that nothing is as he left it, and when a kidnapping rattles the school, Bruce seeks answers as the dark and troubled knight.